Sílicas Mesoporosas SBA-15 modificadas com aminas cíclicas Síntese, caracterização e adsorção de cátions. - Filha., Vera Lúcia da Silva Augusto (2011)
In this work was realized the synthesis of silica SBA-15 at room temperature by acid hydrolysis of tetraethyl ortosilicate (TEOS) in presence of the pluronic copolymer P123 (EO20PO70EO20). The new silylating agents were synthesized from reaction of the commercial reagents 3-glycidoxipropyltrimethoxyisilane (GLIC) and 3- chloropropyltrimethoxysilane (Cl) with the molecule of 1-(2-aminoethyl)piperazine (AMP). The new silylating agents were anchored onto mesoporous silica surface by homogeneous route (HOM). The commercial silylating agents and the amines 1-(2- aminoethyl) piperazine (AMP) and piperazine (PIP) were immobilized in consecutive steps by heterogeneous route (HET). Silica SBA-15 was characterized by X-ray scattering in low angle and nitrogen adsorption-desorption measurement. The new silylating agents were characterized by 13C NMR and infrared spectroscopy. The modified matrices were characterized by infrared spectroscopy, nitrogen adsorption-desorption measurement, CHN and Cl elemental analysis, thermogravimetry, scanning electron microscopy and 29Si NMR. Elemental analysis data indicated that the anchoring of 3.41, 3.01, 0.26, 0.32, 0.46 and 0.34 mmol of nitrogen per gram of the supports SIL-GLIC-AMP-HOMO, SIL-Cl-AMP- HOMO, SIL-GLIC-AMP-HETE, SIL-Cl-AMP-HETE, SIL-GLIC-PIP and SIL-Cl-PIP, respectively. These data demonstrated the efficiency of homogeneous route for immobilization of molecule AMP. The adsorption processes were investigated for copper, nickel and cobalt nitrates at pH 2.0; 4.0; 6.0 and 8.0 for silicas modified with the molecule AMP in different times, where the results indicated that the processes were adjusted to a pseudo-second order kinetic. The modified silicas showed the retention capacity at equilibrium for Co2+, Cu2+ and Ni2+ of 1.40; 2.80 and 4.22 mmol g-1 for SILCl- AMP-HETE, 1.02; 1.87 and 6.87 mmol/g for SIL-Cl-AMP-HETE, 4.50; 9.02 and 2.62 for SIL-Cl-AMP-HOMO and 4.,68; 5.55 and 5.28 mmol g-1 for SIL-GLIC-AMP-HOMO, respectively. The adsorption isotherms were best fitted to Temkin, Henry and Freundlich equilibrium models, evidencing the heterogeneity of adsorption sites onto mesoporous silica SBA.